2006
DOI: 10.1007/s10661-006-7669-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Changes in Freshwater Macroinvertebrate Communities Along a Salinity Gradient Using Artificial Substrates

Abstract: Scientists strive to develop efficient sampling protocols, reducing both the number of samples and processing time required, which can be adapted for use in a broad range of ecosystems. We investigated the accuracy and usefulness of artificial substrates in monitoring the impact of rising salinity on freshwater macroinvertebrate communities. We sampled seven sites along a salinity gradient (from 0.2gL(-1) to 2.6gL(-1)) over a 19-km stretch of the Meurthe River, in northeastern France. All other parameters rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
6
13
1
Order By: Relevance
“…According to these results, the optimum salinity for the species-rich malacocoenosis development is within the range of 200-1100 mg·l -1 . Piscart et al [38] suggested that the intermediate salinity levels may be conducive to both salt sensitive and salt tolerant species in accordance with the intermediate disturbance hypothesis of Connell [8]. This hypothesis assumes that in habitats with low salinity, salt tolerant species tend to be excluded from the competition.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…According to these results, the optimum salinity for the species-rich malacocoenosis development is within the range of 200-1100 mg·l -1 . Piscart et al [38] suggested that the intermediate salinity levels may be conducive to both salt sensitive and salt tolerant species in accordance with the intermediate disturbance hypothesis of Connell [8]. This hypothesis assumes that in habitats with low salinity, salt tolerant species tend to be excluded from the competition.…”
Section: Discussionmentioning
confidence: 85%
“…The increasing salinity (as a concentration of dissolved inorganic ions, further referred to as TDS) in surface freshwater ecosystems is becoming a serious problem worldwide [38,52,21,22], including the Czech Republic, especially in post-industrial structures, such as fl ooded mine subsidences [25,43]. Salinity is also regarded as one of the most important environmental contamination types occurring in freshwater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stones were placed around and on top of each trap to avoid any displacement. Traps were left in situ for 36 days, which is considered an exposure time sufficient to allow the complete substrate colonization (Rosenberg and Resh, 1982;Piscart et al, 2006). After this period, traps were collected and their content was carefully sieved and washed, separating invertebrates from cobbles and organic debris; the rinse-out water was filtered with two nets (255 and 50 mm) in order to separate meiofauna from macrofauna.…”
Section: Methodsmentioning
confidence: 99%
“…Salinity tolerance varies profoundly between species. While some species are known to be salt-tolerant, others react sensitively to increasing salinity levels sometimes even ending up in a decline or disappearance of the population (Williams and Williams, 1998;Piscart et al, 2006b). Accordingly, aquatic biota have been commonly classified by salinity preferences.…”
Section: Introductionmentioning
confidence: 99%